Accuracy of Combined Neutrophil to Lymphocyte Ratio and C-Reactive Protein for Diagnosis of Spontaneous Bacterial Peritonitis Among Cirrhotic Patients - Ali, Asif; Saif, Farjad; Faisal, Ummyia; Noor, Zainab (Biological and Clinical Sciences Research Journal, 2025)
Spontaneous bacterial peritonitis (SBP) is a serious complication of liver cirrhosis associated with high morbidity and mortality. While ascitic fluid analysis remains the diagnostic gold standard, it is invasive and not always feasible. There is a need for simple, non-invasive, and cost-effective alternatives to diagnose SBP early, especially in resource-limited settings. Objective: To determine the diagnostic accuracy of combined neutrophil-to-lymphocyte ratio (NLR) and C-reactive protein (CRP) levels in diagnosing SBP among cirrhotic patients, using ascitic fluid PMN count as the gold standard. Methods: This descriptive cross-sectional study was conducted over six months from April 2024 to September 2024, at the Department of Medicine, Ibn-e-Siena Hospital, Multan. A total of 131 cirrhotic patients with ascites were included through non-probability consecutive sampling. All patients underwent diagnostic paracentesis. SBP was confirmed if PMN count in ascitic fluid was ≥250/mm³. NLR and CRP were assessed using venous blood samples. A cut-off of NLR ≥2.9 and CRP >11.3 mg/dL was used to define SBP positivity. Diagnostic indices were calculated using 2×2 contingency tables. Results: Out of 131 patients, 91 (69.5%) were confirmed to have SBP by ascitic fluid analysis. The combination of NLR and CRP showed a sensitivity of 94.5%, specificity of 85.0%, positive predictive value of 93.5%, negative predictive value of 87.2%, and overall diagnostic accuracy of 91.6%. Stratified analysis revealed consistent diagnostic performance across gender and duration of liver disease. Conclusion: Combined NLR and CRP are accurate, readily available, and non-invasive diagnostic markers for SBP in cirrhotic patients. Their application may complement or, in selected cases, substitute ascitic fluid analysis, improving early detection and outcomes in resource-limited settings such as Pakistan.